Anthropomorphized vs objectified brands: which brand version is more loved? - Elena Delgado-Ballester; Mariola Palazón; Jenny Peláez (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to deal with the role of the human metaphor (anthropomorphism) and consumers' liking for the humanized version of the brand as antecedents of three key components of brand love: self-brand integration, positive emotional connection and feelings of anticipated separation distress. Design/methodology/approach A sample of 399 consumers provided information about a brand from a stated list of 16 brands of clothing. Findings Both anthropomorphism and consumers' liking for the humanized brand have positive effects on specific components of brand love. The results confirm that brand anthropomorphism is only desirable when the humanized version of the brand is attractive for consumers. Research limitations/implications A potential shortcoming is the qualitative technique employed to observe anthropomorphic thought. Collecting ratings of anthropomorphic and non-anthropomorphic traits could be viewed as a method more easily applied in market research surveys. Practical implications Managers have to control how consumers imagine the brand as a human entity because it affects brand love. For example, by tracking consumers' opinions and traits of those people associated with the brand and brand user stereotypes can condition consumers' imagination of the humanized brand. Originality/value Compared to the limited number of studies about the relationship between anthropomorphism and brand love, this study focuses on the effects of anthropomorphism as a process, and not as a personal trait, on brand love. It also relies on consumers' imagination instead of brand personification strategies to stimulate anthropomorphism.
Keywords: 650; Brand love; Anthropomorphism; Anticipated separation distress; Emotional connection; Self-brand integration